Arabidopsis MAP65‐4 plays a role in phragmoplast microtubule organization and marks the cortical cell division site. Issue 1 (28th March 2017) - Li, Haoge; Sun, Baojuan; Sasabe, Michiko; Deng, Xingguang; Machida, Yasunori; Lin, Honghui; Julie Lee, Y‐R.; Liu, Bo
Summary: The evolutionarily conserved MAP65 family proteins bundle anti‐parallel microtubules (MTs). In Arabidopsis thaliana, mutations in the MAP65‐3 gene lead to serious defects in MT organization in the phragmoplast and cause failures in cytokinesis. However, the functions of other Arabidopsis MAP65 isoforms are largely unknown. MAP65 functions were analyzed based on genetic interactions among different map65 mutations. Live‐cell imaging and immunolocalization experiments revealed dynamic activities of two closely related MAP65 proteins in dividing cells. The map65‐4 mutation caused synthetic lethality with map65‐ 3 although map65‐4 alone did not cause a noticeable phenotype. Furthermore, the introduction of an extra copy of the MAP65‐4 gene significantly suppressed defects in cytokinesis and seedling growth caused by map65‐3 because of restoring MT engagement in the spindle midzone. During mitosis, MAP65‐4 first appeared at the preprophase band and persisted at the cortical division site afterwards. It was also concentrated on MTs in the spindle midzone and the phragmoplast. In the absence of MAP65‐3, MAP65‐4 exhibited greatly enhanced localization in the midzone of developing phragmoplast. Therefore, we have uncovered redundant but differential contributions of MAP65‐3 and MAP65‐4 to engaging and bundling anti‐parallel MTs in the phragmoplast and disclosed a novel action of MAP65‐4 at the cortical cell division site.